Contribution of 18F-Fluoro-ethyl-tyrosine Positron Emission Tomography to Target Volume Delineation in Stereotactic Radiotherapy of Malignant Cranial Base Tumours: First Clinical Experience. (12th November 2012) - Graf, Reinhold; Plotkin, Michail; Nyuyki, Fonyuy; Wust, Peter; Wurm, Reinhard; Budach, Volker; Brenner, Winfried; Fahdt, Daniel
Abstract : Increased amino acid uptake has been demonstrated in intracerebral tumours and head and neck carcinomas of squamous cell origin. We investigated the potential impact of using 18 F-fluoro-ethyl-tyrosine ( 18 F-FET)-PET/CT in addition to conventional imaging for gross tumour volume (GTV) delineation in stereotactic radiotherapy of skull base tumours. The study population consisted of 14 consecutive patients with cranial base tumours (10 with squamous cell histology, 4 others). All patients underwent a FET-PET/CT examination in addition to contrast-enhanced CT and 11 patients underwent MRI. All tumours and histologic types showed increased FET uptake. The GTV was defined by all voxels showing hyperintensity in MRI or CT (GTVMRI/CT ) or enhancement in PET (GTVPET ), forming a GTVcomposite that was used for the initial treatment fields. An additional volume of infiltrative growth outside the GTVMRI/CT of about 1.0 ± 2 cm 3 (5% of the conventional volume) was demonstrated by FET-PET only (GTVPETplus ) with significant enlargement (>10% of GTVMRI/CT ) in three patients. From existing data, we found correlation between cellular density and the standardized uptake value (SUV) of FET. We were able to substantially reduce the volume of escalated radiation dose (GTVboost ) by 11 ± 2 cm 3 (24%) of the conventional volume.